Non-Ideal Joints and Friction: A Study on Motorcycle Front Suspension Dynamics. - Alcázar-Vargas, Manuel Gonzalo; Pérez-Fernández, Javier; Escalera-Zamudio, Agustín; Cabrera-Carrillo, Juan Antonio; Castillo-Aguilar, Juan Jesús (My University, 2024)
The front suspension of motorcycles plays a crucial role in their dynamic behavior. Throughout history, various types of frontsuspension have been employed in numerous motorcycles [1,2], including telescopic fork, front rocker arm (telelever), four-barmechanisms (Girder, Hossack), leading link, etc. The most widely used and the only one currently employed in high-performancemotorcycles is the telescopic fork. Traditionally, these types of suspensions featured a thicker lower part, housing the wheel axle and brake caliper support in asingle piece, while the upper part consisted of a cylindrical bar. This design, known as conventional fork, evolved over time intoinverted forks. In these, the larger diameter part is attached to the chassis through the triple trees, while the smaller diameter partis positioned at the bottom. This configuration allowed for minimizing the unsprung mass and improving overall stiffness byincreasing the diameter of the bars. This work focuses on the bending moments and friction generated in the front suspension system during braking. Forces in thefront suspension mechanism during braking are analyzed, identifying various sources of these forces (see Figure 1). On one hand, external loads on the tire and brake system create forces and moments at the bottom end of the front suspension.Some of these forces are compensated by normal reactions in the friction bushings connecting the lower and upper parts of thesuspension. Regarding forces in the axial direction of the suspension, these are compensated by the spring and damper, typically.However, the friction of the bushings (and seals) may not be negligible, especially under severe conditions such as uneven terrainor during ABS operation. The influence of this friction is related to what is known in motorcycling as SAG. In this work, a motorcycle in-plane model ispresented, emphasizing the modeling of friction forces in the front suspension and analyzing their impact on planar dynamics.
Keywords: Motocicletas - Muelles y suspensión; Motorcycle; Front suspension dynamics; Non ideal joints